2010
DOI: 10.3391/ai.2010.5.s1.024
|View full text |Cite
|
Sign up to set email alerts
|

Update on geographic spread of invasive lionfishes (Pterois volitans [Linnaeus, 1758] and P. miles [Bennett, 1828]) in the Western North Atlantic Ocean, Caribbean Sea and Gulf of Mexico

Abstract: The Japanese shore crab Hemigrapsus sanguineus is recorded for the first time from a Black Sea locality: Tomis Marina in Constanţa, Romania. The suggested vector of introduction is as adults in the hull fouling of yachts. The species has not established and salinity requirements for larval development make it unlikely that it will ever establish in the Black Sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
179
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 5 publications
3
179
0
7
Order By: Relevance
“…Regardless of the source, lionfish are now firmly established throughout the western Atlantic Ocean, Caribbean Sea, and Gulf of Mexico (Schofield, 2009(Schofield, , 2010Schofield et al, 2011). From 1985 to 2001, they spread up the Atlantic seaboard from Dania Beach, Florida (Semmens et al, 2004;Whitfield et al, 2007;Morris and Akins, 2009).…”
Section: The Lionfish Invasion: Range Expansion Impacts and Managemmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the source, lionfish are now firmly established throughout the western Atlantic Ocean, Caribbean Sea, and Gulf of Mexico (Schofield, 2009(Schofield, , 2010Schofield et al, 2011). From 1985 to 2001, they spread up the Atlantic seaboard from Dania Beach, Florida (Semmens et al, 2004;Whitfield et al, 2007;Morris and Akins, 2009).…”
Section: The Lionfish Invasion: Range Expansion Impacts and Managemmentioning
confidence: 99%
“…Once they have evaded prevention, early detection, and rapid responses to become established, invasive species create direct, detrimental impacts via predation and competition for resources; indirect impacts by altering habitats and interactions among species; and disruptions of ecosystem structure and function by decreasing or homogenizing biodiversity (Carlton and Geller, 1993;Vitousek et al, 1997;Pimental et al, 2001;Knowlton and Jackson, 2008). In many cases, negative outcomes from invasions impinge heavily on threatened and endangered species or exacerbate problems caused by climate change, pollution, overfishing, and other anthropogenic stresses (Knowlton and Jackson, 2008;Schofield, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The widespread establishment of lionfish populations in the eastern Gulf of Mexico beyond depths accessible to divers (Schofield 2010), and frequent episodic red tide events in the eastern gulf may provide some level of control in shallow coastal habitats as populations expand into nearshore regions. At present, removal of lionfish by divers is probably the most common method of control, but this method is generally applicable to waters shallower thañ 35 m. Lionfish are rarely caught in hook-and-line fisheries but have been reported as incidental catches in some deepwater fisheries (Akins 2012) and are frequent bycatch in commercial trap fisheries (National Marine Fisheries Service, Southeast Fisheries Science Center, Trip Interview Program, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Since 2007, lionfish have spread throughout the Caribbean, reaching the Florida Keys in 2009 (Ruttenberg et al 2012) and the Gulf of Mexico in 2010 (Schofield 2010;Fogg et al 2013). Often strongly associated with reef habitats (Schultz 1986;Biggs and Olden 2011;Claydon et al 2012), lionfish in the western Atlantic Ocean have been found to occupy mangrove (Barbour et al 2010;Claydon et al 2012;Pimiento et al 2015), seagrass (Biggs and Olden 2011;Claydon et al 2012), and lower riverine habitats (Jud and Layman 2012) as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation